Manipulation Techniques in the Novel “Crime and Punishment” by F. Dostoevsky - Adamyan, Vera (ՀՀ ԳԱԱ)
Nowadays, interdisciplinary research is actively developing. Such studies are of importance in literary studies as well. In this article we consider the novel Crime and Punishment by Fyodor Dostoevsky from the position of psychology. In particular, we consider the depiction of manipulation in the novel. We study manipulative strategies and tricks used by the characters to achieve their goals. Particular attention is paid to the manipulative techniques and tactics of manipulator characters: Raskolnikov, Porfiry Petrovitch, Svidrigailov, Luzhin, Dounia. The analysis has shown that practically all the characters in the novel are either manipulators themselves or are subjected to manipulation. The only character in the novel who acts only as a manipulator is Svidrigailov. He is also the most skillful manipulator in the novel. We also show how effective the manipulation was by looking at the reactions of the victims of the manipulation: Rodion Raskolnikov, Dounia, Pulcheria Alexandrovna. Our aim was not only to identify manipulative moves in the novel, but also to show their influence on the plot. В настоящее время активно развиваются такие области литературы, в которых рассматриваются вопросы, лежащие на стыке двух наук: литературы и психологии, литературы и социологии, литературы и философии, литературы и культурологии. В данной статье мы опираемся на достижения психологии, с ее позиций рассматриваем роман Ф.М. Достоевского «Преступление и наказание». Мы, в частности, обращаемся к проблеме манипуляции в романе. Нами исследуются манипулятивные стратегии и уловки, применяемые персонажами для достижения своих целей. Վերջին տարիներին ակտիվորեն զարգանում են գրականության այնպիսի ոլորտներ, որոնք անդրադառնում են երկու գիտությունների՝ գրականության և հոգեբանության, գրականության և սոցիոլոգիայի, գրականության և փիլիսոփայության, գրականության և մշակութաբանության ուսումնասիրությունների խաչմերուկում ընկած խնդիրներին: Այս հոդվածում մենք, մասնավորապես, ապավինում ենք հոգեբանության նվաճումներին: Այս տեսանկյունից մենք դիտարկում ենք Ֆ. Մ. Դոստոևսկու «Ոճիր և պատիժ» վեպը և անդրադառնում ենք մանիպուլյացիայի խնդրին։ Ուսումնասիրում ենք կերպարների կողմից կիրառվող մանիպուլյատիվ տեխնիկան և հնարքները, որոնք նրանք օգտագործել են իրենց նպատակներին հասնելու համար:
Keywords: Social and Humanitarian Sciences